Endogenous Lobby Formation and Endogenous Protection: A Long-Run Model of Trade Policy Determination - Mitra, Devashish (American Economic Review, 1999)
This paper provides a theory of lobby formation within a framework in which trade policy is determined through political contributions. Under certain conditions, free trade turns out to be an equilibrium outcome either when the government has a high affinity for political contributions or when it cares a great deal about social welfare. Moreover, greater inequality in asset distribution results in a greater number of lobbies and, in most cases, more protection for each of these lobbies. Furthermore, industries with higher levels of capital stock, fewer capitalists, more inelastic demand, and smaller geographical dispersion are the ones that get organized. (JEL F10, F13)